PEMANFAATAN TEKNOLOGI INFORMASI SEBAGAI MEDIA PEMBELAJARAN DIGITAL DALAM MENINGKATKAN MINAT BELAJAR SISWA PADA MATA PELAJARAN PAI - Sulistri; Ediansyah; Moch Iqbal (Program Studi Manajemen Pendidikan Islam, 2025)
The use of digital media and information technology in learning has become a fundamental necessity in this modern era. Digital media, such as instructional videos, interactive presentations, and online platforms, have been proven to improve students' understanding, motivation, and interest in learning by providing more interactive and engaging learning. In the context of Islamic Religious Education (PAI), the use of digital media not only strengthens Islamic knowledge but also helps shape students' character and religious attitudes. However, the implementation of this technology still faces challenges such as limited infrastructure, teacher skills, and dependence on the internet. Information technology-based learning also has a significant impact on students' learning interests. With this approach, students are encouraged to learn independently, think critically, and be more active in the learning process. However, most teachers still tend to use conventional methods with textbooks as the primary medium, which can lead to boredom and low student interest in learning. Therefore, the integration of information technology in learning must continue to be encouraged to improve the quality of education and develop a generation that is adaptive to current developments.